Strategi Komunikasi Elite Politik dalam Wacana Penundaan Pemilu 2024 dan Perpanjangan Masa Jabatan Presiden - Hutapea, Edison Bonar Tua; Dwi Nugroho, Doddy; Hidayat, Yayan (Journal of Politics and Policy, 2023)
The emergence of a discourse on postponing elections and extending the president’s term of office is a form of communication planning. the strategy model used is an interactive model where representatives of the government elite who have legitimacy convey the meaning intended to motivate the parties to agree on the discourse of postponing the election and extending the president’s term of office. the purpose of this study is to analyze the strategic model in the discourse on postponing elections and extending the president’s term of office. this research uses qualitative methods with a case study approach to see the complete, complex and dynamic pattern of communication strategies in the emergence of discourse on postponing elections and extending the president’s term of office. this research found a communication breakdown in the discourse on postponing the election caused by negative political prejudice from the public towards the government. the discourse is motivated by the public’s historical memory of the image of message leaders, in this case political actors currently in government who act as message senders. not only that, we identified three things that cause noise to occur in the election postponement discourse, namely (1) semantic and psychological disturbances caused by errors in the language used, (2) disturbances in the frame of mind caused by differences in perception between the communicator and the communicant regarding messages conveyed, and (3) cultural disturbances caused by differences in norms, habits, and values that are believed.